Sociodemographic Differences in Perspectives on Postpartum Symptom Reporting - Benda, Natalie C.; Masterson Creber, Ruth M.; Scheinmann, Roberta; Nino de Rivera, Stephanie; Pimentel, Eric Costa; Kalish, Robin B.; Riley, Laura E.; Hermann, Alison; Ancker, Jessica S. (Applied Clinical Informatics, 2024)
Objective The overall goal of this work is to create a patient-reported outcome (PRO) and decision support system to help postpartum patients determine when to seek care for concerning symptoms. In this case study, we assessed differences in perspectives for application design needs based on race, ethnicity, and preferred language.Methods A sample of 446 participants who reported giving birth in the past 12 months was recruited from an existing survey panel. We sampled participants from four self-reported demographic groups: (1) English-speaking panel, Black/African American race, non-Hispanic ethnicity; (2) Spanish-speaking panel, Hispanic-ethnicity; (3) English-speaking panel, Hispanic ethnicity; (4) English-speaking panel, non-Black race, non-Hispanic ethnicity. Participants provided survey-based feedback regarding interest in using the application, comfort reporting symptoms, desired frequency of reporting, reporting tool features, and preferred outreach pathway for concerning symptoms.Results Fewer Black participants, compared with all other groups, stated that they had used an app for reporting symptoms (p = 0.02), were least interested in downloading the described application (p < 0.05), and found a feature for sharing warning sign information with friends and family least important (p < 0.01). Black and non-Hispanic Black participants also preferred reporting symptoms less frequently as compared with Hispanic participants (English and Spanish-speaking; all p < 0.05). Spanish-speaking Hispanic participants tended to prefer calling their professional regarding urgent warning signs, while Black and English-speaking Hispanic groups tended to express interest in using an online chat or patient portal (all p < 0.05)Conclusion Different participant groups described distinct preferences for postpartum symptom reporting based on race, ethnicity, and preferred languages. Tools used to elicit PROs should consider how to be flexible for different preferences or tailored toward different groups.
Keywords: patient-reported outcomes; obstetrics; symptom information